Optimization of Software Development within the Company - Sitepu, Manisa Febiola (Al'adzkiya International of Computer Science and Information Technology (AIoCSIT) Journal, 2023)
Enterprise software, also known as enterprise application software, is computer software used to meet the needs of organizations rather than individual users. Such organizations include businesses, schools, interest-based user groups, clubs, charities and governments. Enterprise software is an integral part of (computer-based) information systems; a collection of such software is called an enterprise system. These systems handle a number of operations within an organization to improve business and management reporting tasks. The system must process information at a relatively high speed and be usable across multiple networks.